STUDENTS’ ENGLISH VOCABULARY MASTERY USING INTERACTIVE POWER POINT - Gani Akbar; Mega Kartika (English Education Study Program FKIP Universitas Alwashliyah Medan, 2023)
This mini research was conducted with the objective to prove the effect of using interactive PowerPoint on students’ English vocabulary mastery at junior high school. Experimental research design was applied as the research method. The total population was 80 students of the eighth grade students. Cluster random sampling was applied to take out the sample. 80 students were taken as the sample from. The classes were determined as experimental group and control group. Each class consisted of 40 students. A set of test consisted of 35 multiple choice test was administered as research instrument. T-test was applied to analyze the data obtained. The data analysis resulted that t-test value was higher than t-table. This proved that Ha was accepted and Ho was rejected. Thus, it was concluded that interactive PowerPoint gave effect on students’ English vocabulary mastery.